PENINGKATAN MOTIVASI KELOMPOK WANITA TANI SARINAH DALAM PROGRAM HARUM MADU PLUS - Hendajany, Nenny; Aprianti, Ine; Kusmadi, Kusmadi; Setiawan, Audita (Universitas Padjadjaran, 2025)
The Sarinah Farming Women's Group was established following outreach from the Garut Regency Government, which launched the Harum Madu (Integrated Useful Home Page) program. This initiative, introduced by the Garut Regency Agriculture Service, aims to optimize home gardens by planting productive crops. The formation of the Sarinah Women Farmers Group supports this program’s activities. However, over time, a decline in members' motivation has become evident, as seen in decreasing attendance at program activities. To address this issue, a community service initiative led by the PKM team at Sangga Buana University will implement comparative study methods and training. Participants from the Sarinah Women Farmers Group (KWT) will visit a vineyard in Karangsari Village, Karangpawitan District, Garut Regency. Additionally, motivational training will be provided to group members in Cinunuk, Wanaraja, Garut Regency. The success of this initiative will be evaluated through pre-test and post-test assessments. Following the comparative study and training sessions, farmer group members demonstrated renewed enthusiasm for planting grapes as an extension of the Harum Madu program. Kelompok Wanita Tani Sarinah terbentuk setelah adanya sosialisasi dari Pemerintah Kabupaten Garut yang meluncurkan program Harum Madu (Halaman Rumah Bermanfaat Terpadu). Program ini digagas oleh Dinas Pertanian Kabupaten Garut yang bertujuan untuk memanfaatkan pekarangan rumah agar ditanami hal yang produktif. Pembentukan kelompok Wanita Tani Sarinah menunjang kegiatan program tersebut, namun seiring berjalannya waktu kurangnya motivasi dari anggota tani menjalankan program ini, terlihat dari berkurangnya kehadiran di tempat pelaksanaan program. Permasalahan motivasi tersebut akan diselesaikan dengan metode studi banding dan pelatihan dalam kegiatan pengabdian masyarakat oleh tim PkM Universitas Sangga Buana. Peserta Kelompok Wanita Tani (KWT) Sarinah akan diajak untuk mengunjungi perkebunan anggur yang ada di Desa Karangsari Kecamatan Karangpawitan Kabupaten Garut. Pelatihan motivasi diberikan kepada pelaku Kelompok Wanita Tani Sarinah di Cinunuk Wanaraja Kabupaten Garut. Keberhasilan pengabdian ini akan diperlihatkan dari hasil pre test dan post test yang dilakukan. Setelah kegiatan studi banding dan pelatihan, para anggota kelompok tani bersemangat untuk menanam anggur sebagai tambahan dalam program Harum Madu.